On coherence and the implications of a non-multiculturalist coherent liberalism (ALPHA. Journal of Arts, Literature and Philosophy, 2009)
This essay discusses the logical in incoherence associating liberal thought with the development (of multiculturalist proposals, and it identifies the latest implications of being a coherent liberal. For this undertaking, first, we show the contradictions of two multiculturalists authors who also try to call themselves liberal, (Kymlicka and Walzer), and second, we analyze the consequences of one liberal author that rejects multiculturalists approaches (Barry).
Keywords: Liberalism; multiculturalism; differentiated citizenship; equality complex; liberalism egalitarian; liberal repression